2020
DOI: 10.3390/biom10071041
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted LC-MS Metabolomics Differentiates Between Virulent and Avirulent Clinical Strains of Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa is a facultative pathogen that can cause, inter alia, acute or chronic pneumonia in predisposed individuals. The gram-negative bacterium displays considerable genomic and phenotypic diversity that is also shaped by small molecule secondary metabolites. The discrimination of virulence phenotypes is highly relevant to the diagnosis and prognosis of P. aeruginosa infections. In order to discover small molecule metabolites that distinguish different virulence phenotypes of P. aeruginosa, 35 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 68 publications
0
29
0
Order By: Relevance
“…Thus, the length of the FA chain could have a significant effect on the molecules' diffusive properties during infections and in the environment. Importantly, Depke et al [16] recently showed that the metabolite profiles of P. aeruginosa can predict virulence in model systems, further highlighting the importance of small chemical variations of specialized metabolites, such as those described here, as important for virulence. The different FA chain lengths may induce quorum sensing signaling differently depending on the environment.…”
Section: Discussionmentioning
confidence: 61%
“…Thus, the length of the FA chain could have a significant effect on the molecules' diffusive properties during infections and in the environment. Importantly, Depke et al [16] recently showed that the metabolite profiles of P. aeruginosa can predict virulence in model systems, further highlighting the importance of small chemical variations of specialized metabolites, such as those described here, as important for virulence. The different FA chain lengths may induce quorum sensing signaling differently depending on the environment.…”
Section: Discussionmentioning
confidence: 61%
“…Unfortunately, pyoverdine was not detected by our analytical methods, which complicates the interpretation of elevated pyochelin levels. Earlier research has associated elevated pyochelin levels with a virulent phenotype [ 15 , 21 , 22 ], and proteome and transcriptome data show the pchD transcript as being upregulated in tn prmC [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the non-annotated features, it is particularly noteworthy that M187T7, a metabolite with an m/z of 187.1230 and the putative sum formula C 12 H 15 N 2 , displays a significantly differential abundance with approximately 5-fold lower levels in tn prmC and a corrected p -value of 0.0001 in the cellular metabolomics data (fold change ‒2.8 and corrected p -value 0.016 in the exometabolome). The ‘unknown’ metabolite has been identified as a putative biomarker for virulent phenotypes in clinical P. aeruginosa strains in a previous study [ 15 ]. Though its identity and function are unassigned, this finding emphasises the potential importance of the metabolite for pseudomonal virulence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations